David and Jonathan between Athens and Jerusalem - Harding, James E. (Relegere, 2011)
This article seeks to explain what made it possible for modern biblical scholars to ask whether the relationship between David and Jonathan in 1-2 Samuel should be regarded as sexual. The answer is to be found in the way the David and Jonathan narrative was read in the nineteenth century alongside passages in Greek and Roman texts that refer to analogous pairs of friends who had already become, or were on their way to becoming, tropes for homoeroticism.